Relasi Jamaah al Khidmah dengan Pondok Pesantren Assalafi al Fithrah perspektif Educational Marketing - Mastur, Ali (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2023)
The activity of marketing educational services is not a business activity so that schools get students, but is a form of school responsibility to the community regarding educational services that have been, are being, and will be carried out. No matter how big an institution is engaged in services, if it is not introduced to the public, then the educational institution will not develop. Therefore, this study aims to analyze the relationship between Jamaah Al Khidmah and Assalafi Al Fithrah Islamic Boarding School from an Educational Marketing Perspective. This research using a qualitative narrative approach found that Jamaah Al Khidmah and Assalafi Al Fithrah Islamic Boarding School are a Dual Relationship partnership relationship (the broadcasting activities are carried out by Jamaah Al Khidmah while the education is by Pondok Al Fithrah), while the type of marketing Jamaah Al Khidmah is a type of internal marketing. and externally, with strategies through segmentation, targeting and positioning.